Development and Validation of Menstrual Disorder of Adolescent (MenDA) Questionnaire in the Malay Language - Mansor , Nurul Bazilah; Erinna, Mohamad Zon; Afendi , Nik Rafiza; Nik Mahmood, Nik Mohamed Zaki; Che Hashim, Noor Adibah Hanum; Engku Ismail, Engku Husna; Mat Pa, Mohamad Najib (IIUM Medical Journal Malaysia, 2025)
Introduction: Menstrual disorders negatively affect adolescents’ quality of life, with physical discomfort and emotional distress often contributing to anxiety. To address this, the present study aimed to develop and validate the Menstrual Disorder of Adolescent (MenDA) questionnaire for assessing adolescents’ knowledge, attitudes, and practices (KAP) regarding menstrual disorders. Materials and Methods: The questionnaire was systematically developed through literature review, focus group discussions, and expert consultation. Six experts assessed content validity, while face validity was tested among 46 adolescents. A cross sectional validation study was conducted with 485 adolescents. The MenDA tool comprised three domains: knowledge (23 items), attitude (18 items), and practice (21 items). Construct validity was evaluated using exploratory factor analysis with principal component extraction and varimax rotation. Internal consistency was determined using Cronbach’s alpha coefficient. Results: The finalized MenDA questionnaire contained 62 items, structured into three domains. The knowledge domain included 23 items and demonstrated good reliability with Cronbach’s alpha of 0.739. The attitude domain, comprising 18 items, showed a Cronbach’s alpha of 0.711, while the practice domain, with 21 items, achieved a Cronbach’s alpha of 0.793. These results confirmed satisfactory internal consistency across all domains. Factor analysis further supported construct validity, reinforcing the appropriateness of the three-domain structure in evaluating adolescents’ menstrual health KAP. Conclusion: The MenDA questionnaire has demonstrated strong validity and reliability as a tool to assess knowledge, attitudes, and practices regarding menstrual disorders among Malaysian adolescents. It provides an evidence based framework for identifying gaps and guiding interventions to improve menstrual health education and management.